Price capping and peak-load pricing in network industries - Gert Brunekreeft (Albert-Ludwigs-Universität Freiburg, Institut für Verkehrswissenschaft und Regionalpolitik, 2000)
This paper examines the effects of various price-cap rules on peakload pricing. The issue recently gains practical importance in regulated network industries. The formal approach reveals that efficiency properties of various price-cap rules are, notwithstanding some problems, fairly good. A discussion of some practically relevant objections suggests that these objections may be not sufficiently convincing to prohibit (or restrict) peak-load pricing. Overall, a strong case can be made for allowing price-cap regulated firms the flexibility to apply peak-load pricing, if the alternatives are to have either no peak-load pricing or have the regulator prescribe the peak-load structure.
Keywords: D4; L51; L96; 330; regulation; peak-load pricing; network-industries; Netzzugang; Spitzenlastpreis; Anreizregulierung; Telekommunikationsgebühr; Theorie